2023
DOI: 10.3390/ijms24087115
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of MicroRNAs in Predicting Breast Cancer Recurrence—A Systematic Review

Abstract: Identifying patients likely to develop breast cancer recurrence remains a challenge. Thus, the discovery of biomarkers capable of diagnosing recurrence is of the utmost importance. MiRNAs are small, non-coding RNA molecules which are known to regulate genetic expression and have previously demonstrated relevance as biomarkers in malignancy. To perform a systematic review evaluating the role of miRNAs in predicting breast cancer recurrence. A formal systematic search of PubMed, Scopus, Web of Science, and Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A recent study proposed that miRNAs might be fundamental elements involve in the cancer cell dormancy and latent metastases, which are related to the recurrence of BC [146]. As a result, knowing differentially expressed circulating miRNAs and tumor-based miRNAs in early-stage BC patients may offer predictive indicators of relapse before the manifestation of recurrence symptoms [147]. These miRNAs can influence abnormal cellular behavior, relapse risk, and, ultimately, survival outcomes.…”
Section: Use Of Mirnas As Prognostic Marker Of Bc Recurrencementioning
confidence: 99%
“…A recent study proposed that miRNAs might be fundamental elements involve in the cancer cell dormancy and latent metastases, which are related to the recurrence of BC [146]. As a result, knowing differentially expressed circulating miRNAs and tumor-based miRNAs in early-stage BC patients may offer predictive indicators of relapse before the manifestation of recurrence symptoms [147]. These miRNAs can influence abnormal cellular behavior, relapse risk, and, ultimately, survival outcomes.…”
Section: Use Of Mirnas As Prognostic Marker Of Bc Recurrencementioning
confidence: 99%
“…Davey et al carried out a systematic review highlighting the ability of miRNAs to be used as biomarkers predictive of the response of early stage HER-2-overexpressing breast cancers to neoadjuvant chemotherapy and/or anti-HER-2 therapies, with 41 miRNAs showing increased expression in patients who responded to neoadjuvant therapy, and 29 miRNAs with reduced expression in patients who responded [ 62 ]. Bouz Mkabaah et al performed a systematic review of the literature, assessing the role of miRNAs in predicting the recurrence of breast cancer, with a total of 44 miRNAs identified as being useful in this goal [ 25 ]. McGuire et al showed that increased expression of miRNA-21 and miRNA-145 in whole blood samples was associated with non-response to neoadjuvant chemotherapy in luminal breast cancer.…”
Section: Mirnas As Biomarkers Of Breast Cancermentioning
confidence: 99%
“…Since the seminal work of these authors, the role of miRNAs in breast cancer has been further elucidated. For example, previous authors have demonstrated the capabilities of miRNAs to predict breast cancer hormone receptor status, others have evaluated the role of miRNAs as therapeutic options in cancer [ 19 , 20 , 21 , 22 ], and several previous reports have correlated miRNA expression profiles with long-term survival outcomes in malignancy [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Krug et al highlights a proteogenomic technique that may be used to identify clinical and molecular features of specific tumors for the development of tumor-specific treatment targets [18]. Transcriptomic characterization of malignant breast tumors based on microRNAs is a novel approach currently under ongoing investigation [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%